Heroic resuscitation? An attempt to revive Descartes' method: Descartes's method: the formation of the subject of science, by Tarek R. Dika, Oxford, Oxford University Press, 2023, xxii + 382 pp., $115 (hardback), ISBN 978-0-19-286986-9. - Schuster, John A. (Annals of Science)
The text reviews Tarek R. Dika's book "Descartes's method: the formation of the subject of science," which delves into the contentious topic of Descartes' method in Cartesian research. Dika challenges existing interpretations of Descartes' method, focusing on the 'Cambridge Manuscript' of Descartes' Regulae. Dika argues that Descartes' method is more about training the mind to solve problems than following specific rules, which has implications for how Descartes' method is understood in various scientific disciplines. The text critically examines Dika's claims, highlighting the complexities and debates surrounding Descartes' method and its application in scientific research.